Phylogeography, taxonomy, and conservation of the endangered brown howler monkey, Alouatta guariba (Primates, Atelidae), of the Atlantic Forest - Oklander, Luciana I.; Fernández, Gabriela P.; Machado, Stela; Caputo, Mariela; Hirano, Zelinda M. B.; Rylands, Anthony B.; Neves, Leonardo G.; Mendes, Sérgio L.; Pacca, Luciana G.; Melo, Fabiano R. de; Mourthé, Italo; Freitas, Thales R. O.; et al. (Frontiers in Genetics, 2024)
The brown howler, Alouatta guariba, endemic to the Atlantic Forest of Brazil and Argentina, is threatened by habitat loss and fragmentation, hunting, and its susceptibility to yellow fever. Two subspecies have been recognized, but their names, validity, and geographic ranges have been controversial. We obtained samples covering the species entire distribution in Brazil and Argentina to clarify these issues by investigating the species’ genetic diversity and structure and assessing its evolutionary history. We analyzed, for the first time, a set of ten microsatellite markers (N=153), plus mitochondrial DNA (mtDNA) segments of the control region (N=207) and cytochrome-b gene (N=116). The microsatellite data support two to three genetic clusters with biological significance. The southern populations (Argentina, Santa Catarina, Rio Grande do Sul) presented a homogeneous genetic component, and populations from São Paulo (SP) to the north presented another component, although most presented 20% of the southern component. With K=3, SP emerged as a third component while sharing some ancestry with Rio de Janeiro and Argentina. The mtDNA phylogenies revealed three main clades that diverged almost simultaneously around 250 kya. Clades A and B are from central SP to the north and east, while clade C is from SP to the south and southwest. Samples from SP presented haplotypes in all three clades, sometimes in the same population. The demographic history of the species estimated with the Bayesian Skyline Plot of the mtDNA showed a strong expansion 40–20 thousand years ago (kya) and a strong reduction since the last 4–2 kya. Although the genetic clusters identified here deserve appropriate management strategies as Conservation Units, the absence of: (i) concordance between the mtDNA and microsatellite data, (ii) reciprocal monophyly in the mtDNA, and (iii) clear-cut non-genetic diagnostic characters, advises against considering them as different taxonomic entities. None of the previous taxonomic proposals were corroborated by our data. Our results elucidate the taxonomy of the Atlantic Forest brown howler, indicating it should be considered a monotypic species, Alouatta guariba. We also clarify the evolutionary history of the species regarding its intraspecific genetic diversity – crucial information for its conservation and population management.